Subgenome asymmetry of gibberellins-related genes plays important roles in regulating rapid growth of bamboos - Ling Mao; Cen Guo; Liang-Zhong Niu; Yu-Jiao Wang; Guihua Jin; Yi-Zhou Yang; Ke-Cheng Qian; Yang Yang; Xuemei Zhang; Peng-Fei Ma; De-Zhu Li; Zhen-Hua Guo (Plant Diversity)
Rapid growth is an innovative trait of woody bamboos that has been widely studied. However, the genetic basis and evolution of this trait are poorly understood. Taking advantage of genomic resources of 11 representative bamboos at different ploidal levels, we integrated morphological, physiological, and transcriptomic datasets to investigate rapid growth. In particular, these bamboos include two large-sized and a small-sized woody species, compared with a diploid herbaceous species. Our results showed that gibberellin A1 was important for the rapid shoot growth of the world's largest bamboo, Dendrocalamus sinicus, and indicated that two gibberellins (GAs)-related genes, KAO and SLRL1, were key to the rapid shoot growth and culm size in woody bamboos. The expression of GAs-related genes exhibited significant subgenome asymmetry with subgenomes A and C demonstrating expression dominance in the large-sized woody bamboos while the generally submissive subgenomes B and D dominating in the small-sized species. The subgenome asymmetry was found to be correlated with the subgenome-specific gene structure, particularly UTRs and core promoters. Our study provides novel insights into the molecular mechanism and evolution of rapid shoot growth following allopolyploidization in woody bamboos, particularly via subgenome asymmetry. These findings are helpful for understanding of how polyploidization in general and subgenome asymmetry in particular contributed to the origin of innovative traits in plants.